Impact of E-Service Quality of Mobile Application on Customer Perceived Value - Sharma, Rohit Kumar; Padashetty, Sanjeev (Mercados y Negocios, 2025)
The present study examines the effect of mobile app service quality on consumer perceived value (CPV) in online shopping in India, specifically in Bengaluru, and customer satisfaction (CS) on CPV. A quantitative research method was employed, in which data were collected from 222 randomly selected consumers using structured questionnaires and interviews. The analysis was conducted in R Studio, utilizing analyses that included discriminant validity, confirmatory factor analysis, and structural equation modeling (SEM). The findings indicate that mobile app service quality has a significant impact on CPV, with reliability and consumer service being the most critical dimensions. In contrast, content quality was the least essential of the dimensions. Additionally, CS had a significantly positive effect on CPV and partially mediated the relationship between content quality, navigation, visual design, contact, and CPV.